2002
DOI: 10.2460/javma.2002.220.1017
|View full text |Cite
|
Sign up to set email alerts
|

Use of prostaglandins and bromocriptine mesylate for pregnancy termination in bitches

Abstract: Results of this study indicate that protocols that combine the use of bromocriptine mesylate and prostaglandins for the termination of unwanted pregnancy in bitches are efficient and safe. The use of bromocriptine mesylate and cloprostenol had the best results and could be easily used on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Treatment with dopamine agonists that exert antiprolactinergic effect via stimulation of D2 pituitary receptors or inhibition of central serotoninergic receptors from day 35 to 40 can result in abortion (Concannon and others 1987, Post and others 1988, Onclin and others 1993). There are also other methods of terminating pregnancy such as combining prostaglandins and dopamine agonists, studies of which have shown good results and fewer side effects (Onclin and others 1993, Onclin and others 1995, Onclin and Verstegen 1996, Gobello and others 2002). Dexamethasone has also been used to terminate pregnancy in bitches (Zone and others 1995, Wanke and others 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with dopamine agonists that exert antiprolactinergic effect via stimulation of D2 pituitary receptors or inhibition of central serotoninergic receptors from day 35 to 40 can result in abortion (Concannon and others 1987, Post and others 1988, Onclin and others 1993). There are also other methods of terminating pregnancy such as combining prostaglandins and dopamine agonists, studies of which have shown good results and fewer side effects (Onclin and others 1993, Onclin and others 1995, Onclin and Verstegen 1996, Gobello and others 2002). Dexamethasone has also been used to terminate pregnancy in bitches (Zone and others 1995, Wanke and others 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Safe and applicable methods consisting of inexpensive pharmacological agents for abortion are particularly desired. The administration of different abortifacients such as, prostaglandin F2α, dopamine agonists, dexamethasone and progesterone blockers were tested at different doses, alone or in combination for mid-gestation pregnancy termination in dogs (Kaya et al, 2014;Petterson and Tidholm, 2009;Galac et al, 2000;Cetin et al, 2000;Corrada et al, 2006;Hori et al, 2002;Gobello et al, 2002;Onclin and Verstegen, 1999;Feldman et al, 1993;Shille et al, 1984;Wanke et al, 1997;Zone et al, 1995;Onclin and Verstegen, 1996). Great oxygen consumption by feto-maternal unit and alterations in metabolic pathways are the reasons of increased oxidative stress during pregnancy period, leading imbalance between the formation of free radicals and the capacity for defense of the antioxidant mechanisms (Harma et al, 2004;Casanueva and Viteri, 2003;Vannucchi et al, 2007;Krieger and Loch-Caruso, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This association allows to reduce PG dosage and consequently the intensity of the PG side effects (Onclin and Verstegen 1996, 1999; Aslan et al. 2001; Gobello et al. 2002).…”
Section: Introductionmentioning
confidence: 99%